Exploring participants’ experiences of and perspectives on relational development: The cases of CLARISSA SP+ and WORKFREE - Lazarus, Joel (Community Development, 2026)
There is growing engagement with “relational” approaches to community development work - interventions that give practical or even metaphysical primacy to relations and processes over identities and outcomes. But what more can we say about the nature and efficacy of such approaches? CLARISSA SP+ and WorkFREE were two major relational community development intervention and research projects that took place in Bangladesh and India respectively. In this article, I compare the experiences and perspectives of participants in CLARISSA SP+ and WorkFREE to learn more about the nature and efficacy of relational community development. My findings reveal how these projects served to meet participants’ individual and collective psychological and material needs and highlight the transformative power of unconditionality. Whilst my overall findings support the case for advancing relational approaches to community development work, I conclude that more work must be done on theoretical and operational refinement and systematic evaluation.
_eprint: https://doi.org/10.1080/15575330.2025.2609533
Keywords: Relationality; community development; needs; universal basic income

Towards a future we won't regret: A dispatch from 2035 - Simpson, Lea (Brink, 2025)
Earlier this year we spoke to 102 leaders from across the globe to ask: Ten years from now, what will we regret not having done today? This framing turned out to be a powerful device for collective horizon scanning and foresight. Across every conversation there was a sense that this moment demands more from us all, along with a strong eagerness to explore what we can own and act on. More than that, these discussions surfaced direction, hope and a way forward. From CEOs, professors, PhDs, tech founders, heads of UN agencies, frontline leaders, local innovators, public servants and practitioners we heard about some of the shifts that are already happening in pockets around the world.

Shift the status quo: Applying a systems approach to improving adolescent health and wellbeing in cities - A guide for practitioners - Ecorys (Ecorys, 2025)
Healthy Cities for Adolescents Phase II (HCA-II) is a multi-country programme that supports projects working to improve adolescent and young people’s health and wellbeing in intermediary cities. Guided by the principle of shifting the status quo, with adolescents at the centre of this, HCA-II aims to catalyse meaningful changes in how cities function for young people. This guide aims to help you influence the systems that shape adolescent and young people’s health and wellbeing in the cities where they live. You don’t need to be a ‘systems expert’ to use it. It’s designed for anyone working on HCA-II projects (or similar) – whether you’re a project manager, Monitoring, Evaluation and Learning (MEL) lead, consortium partner or youth worker – who wants practical ideas for planning, delivering, and learning from work that aims to make cities fairer and healthier for adolescents. A core focus of this guide is helping projects shift system conditions – the underlying structures, relationships, and beliefs that shape how things work. It’s not about fixing everything at once, but about identifying where small changes, like who’s involved in decision-making, how resources are shared, or how people relate to one another, can unlock bigger, longer-term improvements. Focusing on how our work shifts system conditions helps us move beyond surface-level problems and get to the root causes, like policies, resources, relationships, and behaviours that shape adolescents’ lives. It’s a practical way of thinking and working that leads to more joinedup, fair, and lasting change. This guide is designed to be flexible; dip in and out depending on where you are in your project. It includes practical tools, examples, and ideas across five key areas of systems practice.

Implementing Systems Change - Jain, Vikram; Singh, Vivek; Mundol, Hisham; Gogri, Mirik (2025)
While enthusiasm for systems change has grown steadily over the past decade, we find a significant gap persists between this enthusiasm and execution. Funders attempting to implement systems change consistently face 9 challenges, including unclear outcome attribution, long commitment horizons, and complex stakeholder coordination. When faced with these challenges, it is understandable why many funders find themselves defaulting to patching the system rather than changing it. The pressures are real: boards expect clear metrics, program timelines demand quick wins, and established processes reward predictable outcomes. These institutional realities often nudge funders toward incremental fixes, even when they recognize deeper change is needed. This report names and explores the challenges in implementing systems change and provides steps to navigate them. We draw on the authors’ 14 years of experience implementing systems change programs in the Global South across affordable housing, early childhood education, and gender equity. Foundation leaders (e.g., CEOs, principals, and other executives) can use this guide to implement systems change in their work, finding entry points that align with their foundation’s current capacity, constraints, and strategic objectives. Funders can choose to lean in and make their intent to change the system explicit. Doing so would offer the potential for permanent, transformative change that continues long after the intervention or program ends. This choice requires abandoning the comfort of clear attribution and predictable outcomes and accepting that it may be impossible to claim credit for your contributions. The communities you serve rarely need you to prove exactly which intervention created change, but they do need you to commit to changing the conditions that trap them in cycles of inequity. “Courage is not the absence of fear, but action in spite of it.” – Nelson Mandela

Using the Participation Cube to Conduct Participation Analysis of Development Projects in Zambia and Uganda - Roberts, Tony; Howard, Jo (The Journal of Development Studies, 2025)
Cooke and Kothari argue that the seductive claims of participation often provide cover for shallow and tokenistic development practices that fail to address unequal power relationships. This paper provides a novel mechanism that documents and enables a three-dimensional analysis of (a) who participates (b) at which project stages and (c) at what level of agency and power. No other mechanism was found in the literature for systematically tracing and analysing changes in power relationship along all three dimensions. The application of this ‘participation tracing’ approach to two case study projects in Zambia and Uganda identified new opportunities to address power inequities thus moving in the direction of what Hickey and Mohan refer to as transformative participation. The method has only been applied retrospectively to date. Further research is necessary applying the method proactively in project planning and during implementation as a form of participatory project assessment.
_eprint: https://doi.org/10.1080/00220388.2024.2441713
Keywords: Uganda; Zambia; analysis; cube; evaluation; participation; tracing

Pando Funding: Financing System Change Networks - Ricigliano, Rob (Medium, 2025)
By Robert Ricigliano and Anna Muoio

A workflow for collecting and understanding stories at scale, supported by artificial intelligence - Powell, Steve; Caldas Cabral, Gabriele; Mishan, Hannah (Evaluation, 2025)
This article presents an artificial intelligence-assisted causal mapping pipeline for gathering and analysing stakeholder perspectives at scale. Evidence relevant to constructing a programme theory, as well as evidence for the causal influences flowing through it, are both collected at the same time, without the evaluator needing to possess a prior theory. The method uses an artificial intelligence interviewer to conduct interviews, automated coding to identify causal claims in the transcripts, and causal mapping to synthesise and visualise results. The authors tested this approach by interviewing participants about problems facing the United States. Results indicate that the method can efficiently collect and process qualitative data, producing useful causal maps that capture respondents’ views. The article discusses the potential of this approach for evaluation, enabling rapid, large-scale qualitative analysis. It also notes limitations and ethical concerns, emphasising the need for human oversight and verification.

Adapting ripple effects mapping for evaluating public health initiatives in complex systems: Reflections and recommendations from seven case studies - Creaser, Amy; Dowling, Lisa; Helme, Zoe; Crowther, Jamie; Casana, Lily; Williams, Rachel; Young, Emma; Nobles, James; Hall, Jennifer (Evaluation, 2025)
Ripple effects mapping is a qualitative and participatory method, developed to capture the dynamic nature and interacting elements of an initiative, and its impacts. We present our experiences of using ripple effects mapping to evaluate complex public health initiatives across seven case studies in Bradford, UK. Seven researchers engaged in qualitative reflective practice to capture their individual experiences of using ripple effects mapping within their research and practice; outlining how the method has been adapted and highlighting key reflections and recommendations for implementing ripple effects mapping in the future. We developed ten recommendations, with corresponding strategies, for implementing ripple effects mapping sessions. The recommendations outline how ripple effects mapping can be implemented to improve engagement and anticipate and overcome potential barriers. In doing so, we outline how ripple effects mapping can be used, and adapted, to evaluate various public health initiatives, in research and practice.

A Synthesis of Systemic Action Research Processes in the CLARISSA Programme on Worst Forms of Child Labour - Burns, Danny; Apgar, Marina (Institute of Development Studies, 2024)
This paper describes, synthesises and analyses the work of 25 Action Research Groups that were the heartbeat of the CLARISSA Systemic Action Research programme. The CLARISSA programme worked to create participatory and systemic solutions to the worst forms of child labour in the adult entertainment sector in Nepal, and the leather sector in Bangladesh. The paper explores how the action research groups were set up, and how they worked through key stages of trust and relationship building, generating evidence, building theories of change, planning and taking action, and assessing the effects of that action. The paper, which is a synthesis of the evidence and learning produced in the programme, draws together learning about the process for both ground-level action researchers and those who might fund, design or implement future programmes.

From Local Roots to Global Reach: Global South Intermediaries Driving Just and Equitable Governance - Castells Carrión, Paula (Trust, Accountability and Inclusion Collaborative (TAI), 2024)
In an evolving international development landscape, the push for localization has gained urgency. Global South Intermediary Organizations (GSIs) are emerging as key players, offering a promising pathway to achieving localization programming. To harness their potential, it is crucial to develop a deeper understanding of their functions, structures, and strategies. However, they should complement—not replace—direct funding relationships with grassroots organizations. The Trust, Accountability, and Inclusion Collaborative (TAI) is excited to present this comprehensive analysis by consultant Paula Castell Carrión, highlighting the significant potential of GSIs to drive locally led solutions. As Global North donors seek to increase funding to frontline groups, movements, and activists in Global South contexts, GSIs emerge as strategic partners in localization programming. These organizations possess deep contextual knowledge and established networks that can help bridge the gap between international funders and local implementers. Their potential extends beyond simple fund management to include capacity building, strategic guidance, and advocacy for local priorities in grantmaking decisions. There is a growing number of GSIs fulfilling these roles, who have a track record to deliver governance-related funding to the grassroots. In this new study, TAI´s Paula Castell Carrión examines the evolving role of Global South Intermediaries in advancing localization efforts, with a particular emphasis on achieving equitable governance outcomes. Through a detailed investigation of 4 operational models and practical experiences, this paper aims to provide donors with actionable insights for a more effective engagement with GSIs. Paula's investigation centers on six carefully selected case studies and reflects on broader practices and trends within the funding ecosystem. These cases shed light on the diverse approaches, organizational structures, and strategic interventions employed by GSIs across different contexts. We hope that this research contributes to broader strategies on international development funding by: 1. Providing evidence-based insights into the effectiveness of different intermediary models. 2. Identifying best practices for donor-GSI partnerships. 3. Supporting the development of more equitable and effective governance programming

Raising the Bar: Improving How to Assess Evidence Quality in Evaluating Systems-Change Efforts - Apgar, Marina; Aston, Thomas; Snijder, Mieke; Zwollo, Tom (The Foundation Review, 2024)

Innovation Carve-Outs: Curating the space for innovation - Rahman, Asad; Brink (Brink, 2024)
Over the course of this paper we lay out the basis of the Carve-Out method, an approach that leverages a behavioural framework to allow organisations (even those burdened with layers of bureaucracy and entrenched ideas) to create intentionally designed environments that give people the space, resources and support they need to explore and test new ideas. Ideas that may go on to transform the core of their organisation. The Carve-Out method is based on a simple insight: That if we want to deliver real world, enduring impact then we must recognise that it’s real (often irrational, always human) people that are doing the work of innovating. So to deliver the outcomes we seek for people and our planet then we must explore and unlock the human behaviours that we need to get us there. The Carve-Out method makes this possible by creating the conditions for continuous innovation so that existing teams are empowered to explore solutions and bring those transformational ideas to fruition. To get there, first we look at the idea of the innovation lab or ‘skunkworks’: typically physical spaces, built away from business-as-usual constraints and processes where a small team can move quickly and with relative autonomy. We explore the legacy skunkworks principles have left on our contemporary innovation landscape, for example, how the iPhone was developed by a skunkworks team at Apple, as well as the proliferation of government innovation labs in the public sector. We then go on to examine some of the downsides involved in creating isolated innovation units, particularly the potential disconnect between the innovation process and core business operations, and the result this can have on products that might lack relevance to the market or practical applicability to the company’s mainline business. The second section of the paper looks at another model of organisational innovation, which has been adopted by tech companies such as Google and Netflix. This bottom-up model, exemplified by Google’s ‘20% time’ policy, gave employees the freedom and dedicated resources to explore transformative innovations. The paper looks at how these companies leveraged their employees to fuel ‘strategic risk-taking’, but also how this introduced significant pressure on individuals, and the difficulties in sustaining this level of innovation while scaling over the long term. In the third section we introduce the CarveOut method for organisational innovation: a powerful solution for organisations seeking to foster a culture of ideation experimentation, empower teams, and accelerate the development of impactful innovations and drive sustainable growth. Here we show how systematic, continuous, scalable innovation requires genuine integration and the application of behavioural science practices. This combination allows both for the creation of the space, time, and resources for innovation, as well as carving out the psychological and emotional space necessary for changemakers to thrive and grow within an organisation. Through multiple examples we show how designing and shaping the ‘innovation environment’, it is possible to create an integrated and agile system of organisational innovation that allows for the ‘carving out’ of time, resources and space, but also of cognitive bandwidth and the environmental conditions that enable individuals and teams to take creative risks, embrace new perspectives, and engage fully in the innovation process. We lay out five key principles that underpin the Carve-Out model: 1. Commit to evolving and create structures to enable it 2. Keep the people, change the mindsets 3. Learn fast, fail small 4. Invest and scale in line with confidence 5. Do in order to learn The final section of the paper looks at how the Carve-Out method has been successfully applied in real-world scenarios across a number of sectors. The first story looks at how behaviourally informed features were brought to bear on the Frontier Tech Hub, a programme that supports government officials in the UK Foreign, Commonwealth and Development Office (FCDO) to explore radical, early-stage tech ideas that might solve big development challenges and in doing so, evolve the innovation culture of a government department. In the second story we look at how, after the COVID-19 pandemic led to school closures, Lebanon-based NGO Jusoor worked alongside Brink to explore and test a new way of ensuring access to education for refugee children that would eventually shift the whole education system. And in the third story we explore how the uBoraBora fund for education implementers in sub-Saharan Africa, supported teams to take an experimental approach to exploring and testing key questions to enhance their product or service alongside their businessas-usual, and integrate what they learn with governments’ education systems. We end the paper by asking our readers to imagine what could be achieved if they could dedicate a small portion of their organisation’s time and resources to create the conditions for innovation, so their teams could operate with a different set of rules, and be empowered to explore solutions in a safe and supportive environment. We also provide links to a number of tools and resources created by Brink so others can begin to put the ideas found in this paper into action in their work.

Financing System Health: The Pando Fund - Ricigliano, Rob (Medium, 2024)
By Robert Ricigliano and Anna Muoio

Bridging Learning and Action: How Did CLARISSA’s Participatory Adaptive Management Approach Foster Innovation, Effectiveness, and Stakeholder Empowerment? - Prieto Martin, Pedro; Apgar, Marina; Afroze, Jiniya; Arulanantham, Amit; Hicks, Jacqueline; Karki, Shanta; Mareschal, Sophie; Paul, Sukanta; Snijder, Mieke; Uddin, Forhad; Veitch, Helen (Institute of Development Studies, 2024)
Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) is an evidence and innovation-generation programme funded by the United Kingdom’s Foreign, Commonwealth & Development Office (FCDO), responding to the challenge of the worst forms of child labour (WFCL) in Bangladesh and Nepal. It is a challenge characterised by a poor understanding of its drivers and a lack of evidence on what works to combat it. To handle such fundamental uncertainty, the programme adopts a child-centric and participatory action research approach, which is supported by an adaptive management model to respond better to challenges and opportunities. From its inception, the programme needed to navigate shocks and challenges, such as Covid-19 lockdowns, political upheaval, and sustained budget cuts, which put its capacity to learn and evolve to the test. This paper shares insights emerging from evaluating CLARISSA’s participatory adaptive management (PAM) practices, connecting them with current discussions on adaptive management. It provides an in-depth evaluation of CLARISSA’s PAM approach, exploring how adaptive strategies were implemented and evolved throughout the programme’s life cycle. Multiple cases of adaptation and misadaptation were selected and analysed through a series of in-depth interviews and review of programme documentation, allowing us to assess whether and how the adaptive management practices have been operationalised, the degree to which they led to enhanced decision-making and effectiveness, and their empowering effect on children and other programme stakeholders. Through conceptual analysis and real-world examples, the paper examines the key stages and critical dimensions of PAM, conveying the complexities and dynamism of adaptive management in development work, while highlighting both the successes and challenges encountered in operationalising PAM within CLARISSA.
Accepted: 2024-05-10T08:21:46Z

Putting Relationships First. The case for relationship-centred communities, organisations and systems - Lloyd-Rose, Matt; Robinson, David; Robinson, Immy (The Relationship Project, 2024)

Insights for Influence: Understanding Impact Pathways in Crisis Response - Clark, Louise; Carpenter, Jo; Taylor, Joe (Institute of Development Studies, 2023)
The Covid-19 Responses for Equity (CORE) programme was a three-year initiative funded by the Canadian International Development Research Centre (IDRC) that brought together 20 projects from across the global South to understand the socioeconomic impacts of the Covid-19 pandemic, improve existing responses, and generate better policy options for recovery. The research covered 42 countries across Africa, Asia, Latin America, and the Middle East to understand the ways in which the pandemic affected the most vulnerable people and regions, and deepened existing vulnerabilities. Research projects covered a broad range of themes, including macroeconomic policies for support and recovery; supporting essential economic activity and protecting informal businesses, small producers, and women workers; and promoting democratic governance to strengthen accountability, social inclusion, and civil engagement. The Institute of Development Studies (IDS) provided knowledge translation (KT) support to CORE research partners to maximise the learning generated across the research portfolio and deepen engagement with governments, civil society, and the scientific community. As part of this support, the IDS KT team worked with CORE project teams to reconstruct and reflect on their impact pathways to facilitate South-South knowledge exchange on effective strategies for research impact, and share learning on how the CORE cohort has influenced policy and delivered change. This report presents an overview of these impact pathways and the lessons learnt from a selection of the projects chosen to represent the diversity of approaches to engage policymakers, civil society, and the media to generate and share evidence of the effect of the pandemic on diverse vulnerable groups.
Accepted: 2023-11-10T12:56:06Z

Life Stories From Children Working in Bangladesh’s Leather Sector and its Neighbourhoods: Told and Analysed by Children - Sayem, Mashrique; Sayed, Sayma; Maksud, A. K. M.; Reaz Hossain, Khandaker; Afroze, Jiniya; Burns, Danny; Raw, Anna; Hacker, Elizabeth (Institute of Development Studies, 2023)
CLARISSA (Child Labour: Action-Research-Innovation in South and South-Eastern Asia) has a participatory and child-centred approach that supports children to gather evidence, analyse it themselves and generate solutions to the problems they identify. The life story collection and collective analysis processes supported children engaged in the worst forms of child labour in Bangladesh to share and analyse their life stories. Over 400 life stories were collected from children who worked in the leather supply chain, or who lived and worked in leather sector neighbourhoods. Using causal mapping, 53 children who were engaged in or had experience of the worst forms of child labour collectively analysed the data. This resulted in children’s life stories becoming the evidence base for revealing macro‑level system dynamics that drive the worst forms of child labour. This paper is a record of the children’s analysis of the life stories and key themes they identified, which formed the basis of a series of seven child-led Participatory Action Research groups.
Accepted: 2023-11-07T09:14:57Z

Why are effective feedback mechanisms in cash transfers so important? - Jannat, Mahiratul (CLARISSA, 2023)
The CLARISSA Social Protection Intervention was set us as an innovative social policy intervention for tackling social ills, with a...

Lasting Roots: Naatal Mbay and the Integrated Finance Model in Senegal - Fowler, Ben; Courbois, Laura (USAID, 2023)
This report addresses the well-recognized evidence gap1 on the longer-term impacts created by marketdriven programming; specifically, programming influenced by market systems development (MSD) principles. It does so by presenting the findings of an ex-post study conducted three and a half years after the close of USAID’s Feed the Future Senegal Naatal Mbay Activity (hereafter Naatal Mbay) in 2019. It examines the scale and sustainability of changes resulting from Naatal Mbay’s introduction of an integrated finance model (IFM) – described in Error! Reference source not found. below – in the domestic rice sector. This study is one in a series of ex-post evaluations that are being conducted between 2023-2026 on USAID-funded MSD interventions around the world. This study focused on four questions, noted below in Figure 1. These were addressed using a mix of desk research, 122 key informant interviews with market actors and other stakeholders remotely and in Senegal, focus group discussions with 26 rice producers networks in Senegal, and a validation workshop with USAID/Senegal, implementing partner staff and market actors. Findings were analyzed leveraging the Disrupting System Dynamics (DSD) framework (see Figure 4 in the body of the report) as an analytical tool for understanding systems change.

Using a ‘Partnership Rubric’ in Participatory Evaluations - Snijder, Mieke; Hicks, Jacky; Paul, Sukanta; Arulanantham, Amit; Apgar, Marina; Afroze, Jiniya; Karki, Shanta; Mareschal, Sophie; Prieto Martin, Pedro; Uddin, Forhad; Veitch, Helen (Institute of Development Studies, 2023)
Programmes that aim to tackle complex societal issues, such as the worst forms of child labour, require rich partnerships that bring together different perspectives. CLARISSA’s consortium partnership adopts an empowerment approach to the interventions we deliver and our ways of working together. Part of this approach involves ongoing reflection and learning about how we work together in our partnership, and how this can be adapted if needed. This learning note focuses on a method used in CLARISSA to both reflect on and strengthen how we work in partnerships – the partnership rubric. We found that using the rubric flexibly was key to mitigating some of the challenges of such a complex consortium. This included using it in different sizes of forum, with different levels of preparation. Periodically adapting it for country context and as new partners came on board also helped ensure a shared sense of our preferred ways of working as the project progressed.
Accepted: 2023-07-13T10:20:02Z

Applying Adaptive Management in a Fragile Context – Case Study - Lonsdale, Jane; Green, Duncan; Robertson, Kelly (DT Global, 2023)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

The adoption of innovation in international development organisations: lessons for development co-operation - Kumpf, Benjamin; Jhunjhunwala, Parnika (OECD Publishing, 2023)
Addressing 21st century development challenges requires investments in innovation, including the use of new approaches and technologies. Currently, many development organisations prioritise investments in isolated innovation pilots that leverage a specific approach or technology rather than pursuing a strategic approach to expand the organisation’s toolbox with innovations that have proven their comparative advantage over what is currently used. This Working Paper addresses this challenge of adopting innovations. How can development organisations institutionalise a new way of working, bringing what was once novel to the core of how business is done? Analysing successful adoption efforts across five DAC agencies, the paper lays out a proposed process for the adoption of innovations. The paper features five case-studies and concludes with a set of lessons and recommendations for policy makers on innovation management generally, and adoption of innovation in particular.

Revealing the Relational Mechanisms of Research for Development Through Social Network Analysis - Apgar, Marina; Fournie, Guillaume; Haesler, Barbara; Higdon, Grace Lyn; Kenny, Leah; Oppel, Annalena; Pauls, Evelyn; Smith, Matthew; Snijder, Mieke; Vink, Daan; Hossain, Mazeda (The European Journal of Development Research, 2023)
Achieving impact through research for development programmes (R4D) requires engagement with diverse stakeholders across the research, development and policy divides. Understanding how such programmes support the emergence of outcomes, therefore, requires a focus on the relational aspects of engagement and collaboration. Increasingly, evaluation of large research collaborations is employing social network analysis (SNA), making use of its relational view of causation. In this paper, we use three applications of SNA within similar large R4D programmes, through our work within evaluation of three Interidsiplinary Hubs of the Global Challenges Research Fund, to explore its potential as an evaluation method. Our comparative analysis shows that SNA can uncover the structural dimensions of interactions within R4D programmes and enable learning about how networks evolve through time. We reflect on common challenges across the cases including navigating different forms of bias that result from incomplete network data, multiple interpretations across scales, and the challenges of making causal inference and related ethical dilemmas. We conclude with lessons on the methodological and operational dimensions of using SNA within monitoring, evaluation and learning (MEL) systems that aim to support both learning and accountability.

Theory of Change in complex Research for Development programmes: challenges and solutions from the Global Challenges Research Fund - Chapman, Sarah; Boodhoo, Adiilah; Duffy, Carren; Goodman, Suki; Michalopoulou, Maria (The European Journal of Development Research, 2023)
The United Kingdom Research and Innovation (UKRI) Global Challenges Research Fund (GCRF) aimed to address global challenges to achieve the United Nations (UN) Sustainable Development Goals through 12 interdisciplinary research hubs. This research documents key lessons learned around working with Theory of Change (ToC) to guide Monitoring, Evaluation and Learning (MEL) within these complex research for development hubs. Interviews and document reviews were conducted in ten of the research hubs. The results revealed that only one hub invested in an explicit visual system mapping approach, and that funder timelines, budget constraints and issues with capacity and expertise limited the application of these approaches across all hubs. In contrast, many hubs attempted to deal with visual complexity by means of ether constructing multiple, nested ToCs, or a conscious simplification of complexity through reducing their ToC towards a straightforward and uncomplicated chain model or spherical model. While the former approach had some value, most hubs struggled to find capacity to support the full articulation of nested ToCs. In contrast, the latter approach resulted in ToCs which lacked detail or mechanism articulation, but which nevertheless were often ‘fit for purpose’ in ensuring effective communication and coherence across diverse stakeholders and sub-projects. We conclude that in instances where the reporting, funding and management cycles of complex research for development programmes cannot be adapted to properly support learning-based approaches to ToC development, imposing simplicity in the ToC might be fit for purpose. This might also be preferable to more complex visual approaches that are only partially realised.

How are Research for Development Programmes Implementing and Evaluating Equitable Partnerships to Address Power Asymmetries? - Snijder, Mieke; Steege, Rosie; Callander, Michelle; Wahome, Michel; Rahman, M. Feisal; Apgar, Marina; Theobald, Sally; Bracken, Louise J.; Dean, Laura; Mansaray, Bintu; Saligram, Prasanna; Garimella, Surekha; et al. (The European Journal of Development Research, 2023)
The complexity of issues addressed by research for development (R4D) requires collaborations between partners from a range of disciplines and cultural contexts. Power asymmetries within such partnerships may obstruct the fair distribution of resources, responsibilities and benefits across all partners. This paper presents a cross-case analysis of five R4D partnership evaluations, their methods and how they unearthed and addressed power asymmetries. It contributes to the field of R4D partnership evaluations by detailing approaches and methods employed to evaluate these partnerships. Theory-based evaluations deepened understandings of how equitable partnerships contribute to R4D generating impact and centring the relational side of R4D. Participatory approaches that involved all partners in developing and evaluating partnership principles ensured contextually appropriate definitions and a focus on what partners value.

How Big Things Get Done: The Surprising Factors Behind Every Successful Project, from Home Renovations to Space Exploration - Flyvbjerg, Bent; Gardner, Dan (Macmillan, 2023)
World expert Bent Flyvbjerg and bestselling author Dan Gardner reveal the secrets to successfully planning and delivering ambitious projects on any scale.Nothing is more inspiring than a big vision that becomes a triumphant new reality. Think of how Apple’s iPod went from a project with a single employee to an enormously successful product launch in eleven months. But such successes are the exception. Consider how London’s Crossrail project delivered five years late and billions over budget. More modest endeavours, whether launching a small business, organizing a conference, or just finishing a work project on time, also commonly fail. Why?Understanding what distinguishes the triumphs from the failures has been the life’s work of Oxford professor Bent Flyvbjerg. In How Big Things Get Done, he identifies the errors that lead projects to fail, and the research-based principles that will make yours succeed:- Understand your odds. If you don’t know them, you won’t win.- Plan slow, act fast. Getting to the action quick feels right. But it’s wrong.- Think right to left. Start with your goal, then identify the steps to get there.- Find your Lego. Big is best built from small.- Master the unknown unknowns. Most think they can’t, so they fail. Flyvbjerg shows how you can.Full of vivid examples ranging from the building of the Sydney Opera House to the making of the latest Pixar blockbusters, How Big Things Get Done reveals how to get any ambitious project done – on time and on budget.

Guide to Principles of Emergent Learning - Darling, Edited Marilyn; Eenigenburg, Avery (The Emergent Learning Community Project, 2023)

How Political Contexts Influence Education Systems: Patterns, Constraints, Entry Points - Levy, Brian (Research on Improving Systems of Education (RISE), 2022)
This paper synthesises the findings of a set of country studies commissioned by the RISE Programme to explore the influence of politics and power on education sector policymaking and implementation. The synthesis groups the countries into three political-institutional contexts: - Dominant contexts, where power is centred around a political leader and a hierarchical governance structure. As the Vietnam case details, top-down leadership potentially can provide a robust platform for improving learning outcomes. However, as the case studies of Ethiopia, Indonesia, Nigeria, and Tanzania illustrate, all-too-often dominant leaders’ goals vis-à-vis the education sector can veer in other directions. - In impersonal competitive contexts, a combination of strong formal institutions and effective processes of resolving disagreements can, on occasion, result in a shared commitment among powerful interests to improve learning outcomes—but in none of the case studies is this outcome evident. In Peru, substantial learning gains have been achieved despite messy top-level politics. But the Chilean, Indian, and South African case studies suggest that the all-too-common result of rule-boundedness plus unresolved political contestation over the education sector’s goals is some combination of exaggerated rule compliance and/or performative isomorphic mimicry. - Personalised competitive contexts (Bangladesh, Ghana, and Kenya for example) lack the seeming strengths of either their dominant or their impersonal competitive contexts; there are multiple politically-influential groups and multiple, competing goals—but no credible framework of rules to bring coherence either to political competition or to the education bureaucracy. The case studies show that political and institutional constraints can render ineffective many specialised sectoral interventions intended to improve learning outcomes. But they also point to the possibility that ‘soft governance’ entry points might open up some context-aligned opportunities for improving learning outcomes. In dominant contexts, the focus might usefully be on trying to influence the goals and strategies of top-level leadership. In impersonal competitive contexts, it might be on strengthening alliances between mission-oriented public officials and other developmentally-oriented stakeholders. In personalised competitive contexts, gains are more likely to come from the bottom-up—via a combination of local-level initiatives plus a broader effort to inculcate a shared sense among a country’s citizenry of ‘all for education’.

How and Why Practitioners Think and Work Politically - Evidence from Chemonics Programming Across Sectors - Kantelberg, Renee; Swift-Morgan, Jennifer; Watson, Bryce (Chemonics International, 2022)
Most development practitioners have long recognized that deep contextual knowledge is crucial to understanding how projects interact with their local systems and, in turn, to navigating these systems. Moreover, this knowledge must complement projects' technical solutions, or they will fall flat and may even undercut project objectives as they clatter down. What, then, explains practitioners' particular interest in TWP as an explicit strategy and more than just "doing good development"? This report responds to that question and to the many calls for a more comprehensive picture of TWP by presenting new evidence of the various forms that TWP may take in practice. The evidence comes from a 2022 study that Chemonics undertook to foster more robust learning about TWP. Specifically, we closely examined Chemonics implemented projects that used or are using various forms of TWP in nine countries: Bangladesh, Iraq, Mozambique, the Philippines, Pakistan, Syria, Timor-Leste, and Tunisia. In conducting the study, we interviewed multiple staff from these projects. We complemented what we learned from these projects with a review of eight additional Chemonics- implemented projects applying TWP that had received dedicated support from Chemonics’ Center for Politically Informed Programming (the Center). We consider these findings alongside those of the recent (2022) USAID-Chemonics study on political economy analysis (PEA) usage to identify and articulate what is different and more effective about PEA processes and TWP practices that have received more support.

Study on application of Adaptive Management (AM) in Education Out Loud (EOL) project implementation in the Horn, Eastern adn Southern Africa (HESA) - ANHRE (Oxfam, 2022)
This study mainly aimed to look at adaptive management in the program cycle (throughout Program Cycle processes, including strategy, project, and activity design and implementation) and to look at the Enabling Conditions: how an organization’s culture, business processes, and resource allocation support adaptive management. It explores elements of adaptive management that correspond to the objectives of the study as follows: 1) Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology. 2) Examine how adaptive management has been applied in EOL project implementation thus far. 3) Explore ways in which an adaptive management approach can be used as a source of learning during project implementation. 4) Propose ways in which the application of adaptive management can be improved in EOL project implementation. Objective 1: Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology: The researchers asessed whether the EOL program, GMU, and HESA RMU have a culture of openness, continuous learning, reflection, and improvement. This assessment looked at actual practices and perceptions of field-based staff and project officers. In addition, they looked at processes to assess knowledge management and decision-making process – the ability to distill, share and disseminate knowledge and the awareness among grantees/ employees of the decision-making process. Summary of findings: Understanding of adaptive management as a programming approach among the selected sample of grantees was linked to continuous learning, the ability to adjust implementation and inform decision making to reach the intended objectives based on analysis and assessment of the context and flexibility in management. RMU HESA was perceived to have a culture of openness where grantees feel comfortable sharing their opinion and ideas and is perceived to be receptive to proposed changes to projects and encourage grantees to provide feedback. The HESA RMU-Oxfam Denmark is also seen as an agency that is very “flexible“. Recommendations: Enhance Capacity building on adaptive management tools, particularly for finance and admin teams with a focus on pro-active adaptive management which scans the horizon for opportunities and risks, and it adapts to take advantage of them. It explicitly plans for experimentation and regular upgrading of the strategies; it considers learning and the reduction of uncertainty and imperfect knowledge as one of the key objectives of the management effort. Objective 2: Examine how adaptive management has been applied in EOL project implementation thus far Methodology: Two elements were assessed : Collaboration and how internal and external collaboration of grantees and grant agent, assessing the ability to collaborate with other departments within the entity, the ability to collaborate with learning partners, other grantees, to what extent they consult their stakeholders and their ability to build coalitions. In addition, researchers looked at Adaptation and the best practices and lessons learned in adopting change in the design, implementation, budgeting or monitoring of EOL programs and the process followed to adapt the desired change. Summary of findings: Adaptive management practices are seen to be adapting to context changes, constant learning, and flexibility. The management and coordination of EOL program is deemed to be collaborative, adaptive, and understanding of the emerging needs of EOL Program implementation. There is a simple process in place for grantees to make changes to the program implementation. Most grantees do take the time to pause and reflect on what is going well and what could be improved and to share the knowledge gained with their coalition members and regional coalitions. HESA RMU was found to be encouraging learning practices through organizing periodic online and offline regional learning and reflection workshops. Compared to other donors, the majority of grantees believe that EOL provided the highest level of flexibility and ability to adapt which is seen to be a necessity for advocacy work. However, it is important to enforce structure to tighten the feedback loop between data and action: adaptive management aims for double learning more than just correcting deviations in planned versus actual. Recommendations: Introducing outcome harvesting tool as one of the mechanisms to capture outcomes, institutionalization of adaptive management further by developing context analysis tools/ regular reviews of TOC. Further use of Scenario planning as a tool to map and plan different scenarios on how change may happen, and to examine the program’s role in making future events happen, enforcing structure to tighten the feedback loop between data and action. In addition to the introduction of quarterly planning cycles where data and information gathered in the previous quarter can be used to inform the next planning cycle and update the TOC, project design and activity implementation strategies. Objective 3: To explore ways in which an adaptive management approach can be used as a source of learning during project implementation Methodology: The team assessed the grantees’ ability to use evidence to build their pathways for change, their ability to use learning to inform decision making, the frequency and habit of reviewing their theory of change, the risks and opportunities through scenario planning, how they assess the efficiency of their data collection tools and monitoring and evaluation data quality, on whether they have a mechanism to monitor unintended outcomes (outcome harvesting) and reflect. Summary of findings: This study revealed that there is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program has adopted Re-active Adaptive Management that relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. Recommendations: Encouraging further engagement on knowledge sharing hubs and investing in knowledge transfer on adaptive management and learning to other partners in targeted countries (EOL to become an influencer in this field), encouraging further engagement from learning partners to provide mentorship and support during implementation and continuous learning on adaptive management tools. RISP and GISP could be further engaged in the monitoring process. Based on the stated objective, what was assessed and findings, it would also be interesting to enable grantees distill learnings from AM practices and applying that knowledge to improve project implementation. This means AM will be expected to go beyond changing implementation strategies and budgets and document learnings from such changes and apply them to improve the remaining part of the project. Objective 4: Propose ways in which the application of adaptive management can be improved in EOL project implementation Summary of findings: Grantees were able to articulate well their understanding of adaptive management but were less able to provide concrete examples of how adaptive management is implemented in practice. There is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. However, it is important to enforce structure to tighten the feedback loop between data and action and to institutionalize practicing adaptive management. Recommendations: A roadmap that looks at reviewing seven steps for improving adaptive management is recommended as a systematic tool to introduce improvement. This roadmap is useful in a multi-organizational, multi-country set-up where efficient design is needed to align top-down structuring and requirements with bottom-up diversity and divergence. This roadmap of seven steps is introduced by HIVOS. These 7 steps can come in a different order and it depends on the user to assess which of the seven steps needs to be undertaken. 1. Annual Review results/ outcome statements: using outcome harvesting to continuously monitor intended/ unintended outcomes (whether positive or negative or within the sphere of control (outputs) or within the sphere of influence (outcomes). 2. Learning questions: Learning from the monitoring data; Learning about the critical Make-or-Break assumptions in the Theory of Change; and Developing learning topics/ questions and learning agenda at each level 3. Changes in context: Identifying possible trends and signs about emerging shifts in the environment, followed by analyzing and collective sense-making of possible implications for the Theory of Change (is there a need to revise intervention strategies, desired outcomes, pathways, assumptions? 4. Theory of change: Reviewing the theory of change was not seen as a frequently recommended practice. Constant validation of pathways to change and evidence in the TOC is important. 5. Capacity assessment and development: What capacities are available amongst the alliance members and partner organizations in relation to the (revised) Theory of Change; What would be Capacity Development needs in view of the capacity assessment results? 6. Strategies and interventions: With the outcomes achieved and learning so far, what can you say about your interventions and strategies? What worked? Why? Is there a need for adjustment? 7. Annual reflection and Planning Who should take part in the annual planning and reflection?

Learning from Life Story Collection and Analysis With Children Who Work in the Worst Forms of Child Labour in Nepal - Karki, Shanta; Apgar, Marina; Snijder, Mieke; Sharma, Ranjana (Institute of Development Studies, 2022)
The CLARISSA Nepal team collected and analysed 400 life stories of children and young people engaged in or affected by the worst forms of child labour (WFCL), particularly in the “Adult Entertainment” sector in Nepal, which includes children working in Dohoris (restaurants playing folk music), dance bars, spa-massage parlours, khaja ghars (tea/snack shop) and guest houses. Stories were also collected from children in CLARISSA’s focus neighbourhoods, children in this category include street connected children and those working in transportation, party palaces, domestic labour and construction sites. Of the 400 stories collected, 350 were collected by adult researchers and 50 were collected by children themselves.
Accepted: 2022-11-04T12:22:13Z

‘Fake seeds cost us money’: Learning from Traction’s adaptive approach to changing the stakes for farmers in Malawi - Kelsall, Tim; Laws, Ed (2022)
Improved seed has the potential to boost crop yields and improve livelihoods for millions of small farmers in Malawi. Yet many small farmers are not using it. The reasons are numerous, but one of the most important is the prevalence of fake seed in the marketplace. Improved seed is more expensive to produce and sells for a much higher price than normal seed and grain, providing an incentive for unscrupulous traders to cheat farmers, using various tricks such as filling improved seed packets with normal grain or stocking shops with authentic seed, while delivering fake seed from warehouses. Such practices weaken confidence in the improved seed market, holding back agricultural development and poverty reduction. FCDO’s Traction, a politically smart, issue-based, adaptive development programme, set out to solve this problem using scratch cards – a technical solution that helped farmers verify the authenticity of the seed they were purchasing. After approximately two years of working on the programme, scratch cards on seed packaging have become mandatory for the pivotal crops of maize and legumes. This briefing, based on programme documentation and nine interviews with Traction staff and stakeholders, tells the story of how this breakthrough was achieved, focusing on the novel methodology Traction employed, some of the programme’s twists and turns, and what the experience tells us about issue-based programming in places like Malawi.

Thinking and Working Politically in the Land Sector in Mekong Region - Burns, Tony; Ingalls, Micah; Rickersey, Kate (2022)
In recent decades, the World Bank and many bilateral development partners have provided funding to support land administration reform. Traditional land administration reform projects focus on the economic and technical design of interventions based on a library of best practice, commonly avoiding the “messy politics” typically involved in land governance. Experience and lessons from land administration reform initiatives have been documented and a recurrent theme is that many projects fail to create effective, transformative change and gain the critical mass, and the community participation, necessary to ensure the sustainability of land administration reform. Over the last decade there have been concerted efforts to develop more politically informed ways of thinking and working using a range of methodologies referred to, variously, as Thinking and Working Politicallyi (TWP), Problem Driven Iterative Adaptation (PDIA) and Doing Development Differently (DDD). There is little evidence that these different approaches have been applied in the land sector.

Evidence-led adaptive programming: Lessons from MUVA - Sharp, Samuel; Riemenschneider, Nils; Selvester, Kerry (ODI, 2022)
Calls for more ‘adaptive programming’ have been prominent in international development practice for over a decade. Learning-by-doing is a crucial element of this, but programmes have often found it challenging to become more learning oriented. Establishing some form of reflective practice, against countervailing incentives, is difficult. Incorporating data collection processes that generate useful, timely and practical information to inform these reflections is even more so.This paper explores MUVA - an adaptive female economic empowerment programme in Mozambique. MUVA, we suggest, is atypically evidence-led. It combines systematic, inclusive reflective practice with extensive real-time data collection. We describe the fundamental features of MUVA’s monitoring, evaluation and learning (MEL) approach that supported this. One, how data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, how MEL systems are designed to prioritise actionable learning, with data collection oriented more to the needs of implementing staff than to the reporting requirements of funders.This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators. We conclude by considering the relevance, or not, of MUVA’s approach to programmes in other contexts or issue areas trying to replicate a similarly evidence-informed approach to adaptive management. Key messages Learning-by-doing is essential to adaptive programming, but it can be challenging to establish data collection processes that generate useful, timely and practical information. MUVA – a female economic empowerment programme in Mozambique – has an atypically evidence-led adaptive management approach. This has two fundamental features. One, data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, data collection is oriented more to the needs of implementing staff than to the reporting requirements of funders. Monitoring, evaluation and learning (MEL) systems are designed to prioritise actionable learning. This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators.

Using stories in evaluation: Participatory Narrative Inquiry and Sensemaking (2022)
Sensemaking and Participatory Narrative Inquiry (PNI) are similar approaches, based on collecting stories about a real life experience from a large number of stakeholders on a topic of interest to the evaluation, and giving the storytellers themselves the responsibility for analyzing and making sense of the stories. Because a large number of stories are collected and self-interpreted, it is possible to conduct quantitative analysis of recurrent themes, perspectives and feelings emerging in the narratives. By combining elements of qualitative and quantitative research, these approaches help to make sense of complex and evolving realities. This session presented the general approach of Sensemaking and PNI. Panelists discussed their experiences with this method, recently used in IFAD and WFP’s evaluations and invited participants to share their own experiences with using stories in evaluation.

Thinking and Working Politically on Health Systems Resilience: Learning from the experience of Cameroon, Nepal and South Africa during COVID-19 - Williams, Gareth (TWP Community of Practice, 2022)

Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (Institute of Development Studies, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.
Accepted: 2022-04-25T10:25:54Z

Ripple effects mapping: capturing the wider impacts of systems change efforts in public health - Nobles, James; Wheeler, Jessica; Dunleavy-Harris, Kirsty; Holmes, Richard; Inman-Ward, Alan; Potts, Alexandra; Hall, Jennifer; Redwood, Sabi; Jago, Russell; Foster, Charlie (BMC Medical Research Methodology, 2022)
Systems approaches are currently being advocated and implemented to address complex challenges in Public Health. These approaches work by bringing multi-sectoral stakeholders together to develop a collective understanding of the system, and then to identify places where they can leverage change across the system. Systems approaches are unpredictable, where cause-and-effect cannot always be disentangled, and unintended consequences – positive and negative – frequently arise. Evaluating such approaches is difficult and new methods are warranted.
Keywords: Complex adaptive systems; Complexity; Evaluation; Public health; Systems approach; Systems science

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid delivery more adaptive, relying on principles such as context sensitivity, flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering social transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implications in practice. Purpose The article aims to provide evidence on an adaptive project and demonstrate how the social transformative and political nature of adaptive development management is rendered technical and depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy framework that is implemented through CSOs in Uganda and Vietnam. Data were collected by means of interviews, participant observation and document analysis. Findings We find that, in practice, the social transformative policy framework is competing with managerial logics. We compare this process with the depoliticization of the Paris Declaration on Aid Effectiveness, finding striking similarities. By using practice theory, we show how managerialism remains the dominant paradigm in the civil society aid sector, fuelling the “anti-politics machine.” Policy implications The article shows that policy frameworks do not always work as intended. Donors should therefore not only change policy frameworks, but also start addressing institutional and operational requirements.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12630

Nimble adaptation: Tailoring monitoring, evaluation, and learning methods to provide actionable data in complex environments - Serpe, Lauren; Ingram, Mason; Byom, Kate (New Directions for Evaluation, 2022)
This chapter examines good practices in implementing effective Monitoring, Evaluation, and Learning (MEL) systems within complex international development Democracy, Human Rights, and Governance (DRG) programs, which are characterized by challenges of non-linearity, limited evidence of theories of change, and contextual and politically contingent nature of outcomes. The chapter presents three cases of MEL systems in complex projects implemented by Pact across distinct and diverse operating contexts – Zimbabwe, Cambodia, and Somalia – to illustrate those projects’ MEL approaches that enabled continuous adaptation. The authors analyze the cases to respond to two questions: (1) What are the key elements of effective adaptive management-focused MEL systems in complex environments? (2) What is practical guidance for designing and enabling complexity-responsive and effective adaptive management-focused MEL systems? The case studies illustrate three key elements: (1) Information gathering that closely links context, research, and performance data; (2) Systems for reflection that offer scheduled learning moments of varying frequency and intensity, as well as multiple feedback mechanisms; and (3) Enabling structures that promote adaptive mindsets and attitudes within project teams.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20523

Twenty years of UK governance programmes in Nigeria - Piron, Laure-Hélène; Cummings, Clare; Williams, Gareth; Derbyshire, Helen; Hadley, Sierd (ODI, 2021)
This Flagship report analyses 20 years of governance programmes in Nigeria funded by the UK Department for International Development (DFID) and the Foreign, Commonwealth and Development Office (FCDO) in the North-western states of Jigawa (since 2001), Kano (since 2005) and Kaduna (since 2006), as well as the North-eastern state of Yobe (since 2011). The report’s main research question is whether, how, under what conditions and for whom UK-funded state-level governance programmes in Nigeria have contributed to sustained changes in governance, and related changes in health and education. ... The report concludes with the following recommendations: To international development partners: 1. Invest for the long term – 10 to 20 years – combining support for both state and nonstate actors. 2. Ensure programmes have the strategic-level mandate, managerial capacity and frontline staff skills to pursue politically savvy opportunities. 3. Take PEA to the next level by unpacking causal mechanisms, understanding incentives and designing interventions to make change happen. 4. Give governance programmes the ability to flex between core governance and service delivery issues. 5. Incentivise greater collaboration between governance and sector programmes. 6. Incentivise greater attention to gender, and to social inclusion beyond disability issues, in governance programming. To FCDO: 7. Empower and resource FCDO teams to enable TWP programmes, ensuring decision-making by country teams to respond to local priorities. 8. Re-imagine TWP for FCDO Nigeria, giving implementers the space to operate in TWP ways. 9. Incentivise stronger collaboration between PERL, Lafiya (health programme) and the Partnership for Learning for All in Nigerian Education. 10. Invest in impact data analysis. To partner governments in Nigeria and beyond: 11. Explicitly set out the objectives for which you would like to receive assistance. 12. Use TWP principles to decide how development partners can support your political objectives and the scope for politically-feasible and mutually-beneficial collaboration. 13. Invest in the coordination of development partners. To non-state partners in Nigeria and beyond: 14. Join coalitions to achieve your priorities. 15. Select development partners which can strengthen your skills, not just fund your activities.

Designing a Participatory Programme at Scale: Phases 1 and 2 of the CLARISSA Programme on Worst Forms of Child Labour - Burns, Danny; Apgar, Marina; Raw, Anna (Institute of Development Studies, 2021)
CLARISSA (Child Labour: Action-Research-Innovation in South and South-Eastern Asia) is a large-scale Participatory Action Research programme which aims to identify, evidence, and promote effective multi-stakeholder action to tackle the drivers of the worst forms of child labour in selected supply chains in Bangladesh, Nepal, and Myanmar. CLARISSA places a particular focus on participants’ own ‘agency’. In other words, participants’ ability to understand the situation they face, and to develop and take actions in response to them. Most of CLARISSA’s participants are children. This document shares the design and overarching methodology of the CLARISSA programme, which was co-developed with all consortium partners during and since the co-generation phase of the programme (September 2018–June 2020). The immediate audience is the CLARISSA programme implementation teams, plus the Foreign, Commonwealth & Development Office (FCDO). This design document is also a useful reference point for other programmes trying to build large-scale participatory processes. It provides a clear overview of the CLARISSA programmatic approach, the design, and how it is being operationalised in context.

Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

PDIA in action - Andrews, Matt; Samji, Salimah (Center for International Development, Harvard University, 2021)
Learning from our experience in 2020, we asked the alumni of our HKS Implementing Public Policy (IPP) Executive Education program, if they wanted to work with our students on their nominated problems. Eight IPP alumni, William Keith Young, Adaeze Oreh, Milzy Carrasco, Kevin Schilling, Artem Shaipov, George Imbenzi, David Wuyep, and Raphael Kenigsberg, who had been trained on PDIA and implementation, signed up to work with our students. Thirty-seven students signed up to take the course beginning January 26th, 2021. The students worked across eight teams and adopted a problem driven approach to foster learning that could help their authorizers develop an action learning strategy to their nominated challenge. This book highlights the students’ work drawing from their blogs as well as the event series. There are 8 sections, one for each of the teams and the problems they worked on during the course. We hope you enjoy reading their stories! Scan the QR Code at the end of each section to learn more.

Lessons learned from PERL and partners' response to the COVID-19 crisis - Sharp, Samuel; Nwachukwu, Tochukwu; Srivatsa, Sripriya Iyengar (PERL Programme, 2021)
The first case of COVID-19 in Nigeria was confirmed on 27 February 2020, with the first lockdown orders issued on 30 March 2020. The pandemic and resultant containment measures have had farreaching socio-cultural, economic, financial and political implications, globally as well as in Nigeria. For the Partnership to Engage, Reform and Learn (PERL) and its partners, the pandemic has required considerable adaptation of their strategic approach and working practices. This report reflects on how COVID-19 changed the operating context for PERL’s partners, how PERL responded and what lessons have been learned across delivery teams. For government partners, the most substantial impacts have been to budgets, struck by falling oil prices and reduced economic activity. Universally, states have had to adjust budgets and reforecast, revising budgets downwards and shifting the focus of expenditure towards healthcare. The World Bank’s State Fiscal Transparency, Accountability and Sustainability (SFTAS) Programme has generated powerful incentives for this budget revision, which PERL has been able to work alongside. A range of new governance structures – such as public response committees and task forces – have been established to deal with various aspects of COVID-19 policy, and PERL has had to grapple to maintain its ongoing engagement with these. For civil society organisations (CSOs), the closure of offices from 30 March 2020 has changed the nature of engagement with government. CSOs often developed innovative approaches to maintaining access, including use of social media and direct calls. But the shift to virtual working has been challenging for many CSOs, both in terms of covering the costs of data for virtual meetings and the risks of disengagement and marginalisation for some organisations. In response to this changed context, from March 2020 PERL began to restrategise. The flexible nature of the programme’s workplans, progress markers and budgets enabled activities to be adjusted in a relatively timely manner, with a new workplan approved by the end of April 2020. Central PERL management developed a COVID-19 response strategy which provided a broad framework for adaptations, but allowed substantial autonomy to state and regional teams to lead on reprioritisation according to their understanding of the local context. This was valued by both management and delivery staff. Challenges manifested themselves more in effectively delivering on these adapted workplans than in the process of restrategising – due to two rounds of budget cuts, the merger of DFID and the FCO to form the Foreign, Commonwealth and Development Office (FCDO) and the difficulties of engaging partners virtually. Overall, the pandemic undoubtedly delayed activities (by roughly three months for deprioritised areas of work), but resulted in an array of new, tailored interventions under its broad categories of work. Interventions relating to the health sector became more prevalent, as did work supporting budget adjustments. Domestic resource mobilisation and education interventions were often adjusted to be more relevant to the COVID context or experienced delay. The report provides short illustrative case studies of PERL’s adaptations to: support budget revisions; work with media partners on COVID-19 sensitisation; tracking and advocacy for palliative distribution; and support for the introduction of tax relief. There is some evidence, albeit partial, that PERL was able to take advantage of windows of opportunity offered by the pandemic to drive ahead with certain ongoing reform initiatives.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Adaptive Management: Learning and Action Approaches to Implementing Norms-shifting Interventions - McLarnon, Courtney; Gayles, Jennifer; Deepan, Prabu (USAID / Passages, 2021)
What Passages has Learned about Adaptive Management: • Be reflective about information that is collected and create a culture of learning. • Be systematic about establishing monitoring and learning systems. • Be strategic about data sources and analysis, prioritizing areas for learning and addressing issues raised. • Be inclusive about information collection: who is collecting what, how, and how is it being used.

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/poms.13492

Pushing boundaries: Advocacy evaluation and real-time learning in an HIV prevention research advocacy coalition in sub-Saharan Africa - Dasmariñas, Jules; Schlangen, Rhonda (New Directions for Evaluation, 2021)
Evaluation processes that facilitate learning among advocates must be nimble, creative, and meaningful while transcending putative performance and accountability management. This article describes the experience, lessons, and trajectory of one such approach, Simple, Participatory Assessment of Real Change (SPARC), that a transnational HIV prevention research advocacy coalition pilot-tested in sub-Saharan Africa. Inspired by the pioneering work of the outcome harvesting (OH) and participatory evaluation community, we recuperate advocates' centrality as storytellers, sense-makers, and strategists in advocacy evaluation and describe how we recalibrated SPARC to meet their evaluation and learning needs. This article highlights the normative value of deliberative discourse in evaluation as it contributes to the interpretation of OH and the enrichment of the theory and practice of advocacy evaluation.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20474

Risk navigation for Thinking and Working Politically: The work and disappearance of Sombath Somphone - Sims, Kearrin (Development Policy Review, 2020)
Abstract Motivation On December 15, 2012 Sombath Somphone was abducted at a police checkpoint in his home city of Vientiane, the capital of Laos; his whereabouts remain unknown. This article considers his work and disappearance through the lens of Thinking and Working Politically (TWP) approaches to development. The article is supportive of TWP, but emphasizes the significant risks of politicized programming in authoritarian contexts. Purpose By examining the case of Sombath Somphone, the article seeks to offer insights for safer, and more effective, TWP programming. It considers how specific events in authoritarian contexts can suddenly reposition development workers and/or organizations as political dissidents. Approaches and Methods The argument draws on analysis of grey literature; conversational and observational knowledge accrued during 18 months of fieldwork in Laos between 2011 and 2018; on‐going formal and informal interviews with members of Laos’ civil society sector; and extensive dialogue with Sombath Somphone’s wife, Ng Shui Meng. Findings The article identifies four key factors that contributed to the enforced disappearance of Sombath Somphone: international exposure; timing; particular elites; and strategies of oppression. It highlights the need for further consideration of how to anticipate and mitigate the dangers of politically oriented development work, as well as the different forms of risk experienced by local and international development actors working in authoritarian contexts. Policy Implications TWP has much to offer to development practice, but its contributions should not threaten the safety of local development actors. More attention must be given to preventing and mitigating such risks.

Nuru Kenya transition from Nuru International, Kenya - Dillan, Haley; Ouma, Joel; Yamron, David (What Transformation Takes - Evidence of Responsible INGO Transitions to Locally Led Development Around the World, 2020)
This case study is an example of a phased transfer of ownership and responsibility from INGO Nuru International to Nuru Kenya, including the exit of all international staff. Post-transition, Nuru Kenya is managed entirely by Kenyan staff, although it continues to receive financial support from Nuru International. A lot of the elements described are aligned with Adaptive Management ways of working.

Inspiring Radically Better Futures - Evidence and Hope for Impact at Scale in a Time of Crisis - Guijt, Irene; Mayne, Ruth (Oxfam, 2020)
The world faces converging crises of health, climate, gender and racial injustice and extreme economic inequality. The calls are mounting to ‘build back better’ to create more inclusive, caring and environmentally sustainable futures. But what evidence exists that this is possible? The Inspiring Better Futures case study series investigates whether radical change at scale is possible and how it was achieved. This paper synthesises 18 cases which show that people are already successfully building better futures, benefitting millions of people, even against the odds in some of the world’s toughest contexts in lower-income countries. Together they offer hope that transformative change and radically better futures after the pandemic are within reach.

Adaptation in practice: lessons from teenage pregnancy programmes in Sierra Leone - Castillejo, Clare; Buell, Stephanie (ODI, 2020)
A discussion of initial learning emerging from the SLRC ’Adaptive approaches to reducing teenage pregnancy in Sierra Leone’ action research project.

Shifting Relationships with Grantees: Advancing Trust-Based Philanthropy through Emergent Learning - Gaspari, Brittney (The Emergent Learning Community Project, 2020)

The Hidden Life of Theories of Change - Ho, Wenny; Tamas, Peter; van Wessel, Margit (Hivos, 2020)
Theory of Change is thought to be very useful for learning and adaptive management of complex interventions such as advocacy. Nevertheless, the use of Theory of Change is also under critique. One common criticism is that Theory of Change is often used as a framework that fixes agreements rather than as a living, guiding tool that helps reflection and adaptation. However, while such criticism stresses forms of control, little research has looked at the way Theory of Change and advocacy practice relate. This is a pertinent issue considering that formally agreed Theories of Change and realities on the ground can be very different. This raises questions: Do advocates work in ways different from what Theory of Change states, and if so, how, and why? How does the way they strategize relate to formal Theories of Change? With what implications? In this brief, we explore these more hidden aspects of the life of Theories of Change.

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.

A Theory of Change of citizen participation: an update - Peña-López, Ismael (ICTlogy, 2020)
when it was reduced to a subsidiary internal service lacking all kind of political attributions. The work done in those years had been formidable, but too many things had passed since, especially the 15M Spanish Indignados Movement, the raise of technopolitics… and the raise of populism and fascism all across Europe. We urgently needed a theoretical framework in which to substantiate our political strategy, so I came up with a Theory of Change of citizen participation (see Figure 1) which defined four expected impacts of our political action: 1. Efficiency, efficacy and legitimacy of public decisions improves. 2. Populism has decreased in institutions and the public sphere. 3. Citizens understand the complexity of public decision-making. 4. Citizen participation and political engagement clearly shifts towards a technopolitical paradigm. These impacts were expected to be achieved after some outcomes resulting from some outputs grouped in five programmes: 1. Programme of citizen participation. 2. Programme of internal participation. 3. Programme of collaboration. 4. Programme of intermediaries, facilitators and infomediaries. 5. Programme of e-participation, e-voting and technopolitics. 20 months after, the Theory of Change of Citizen Participation has worked quite well. But it does have some limitations, especially at the operational level-which is what the whole thing was about, to help in putting some order in our daily work.

USAID Wildlife Asia as a case study in adaptive rigour - Ziegler, Jessica (ODI/GLAM, 2020)
This briefing note looks at how the United States Agency for International Development (USAID) Wildlife Asia programme has operationalised the concepts of adaptive rigour and adaptive management as part of its approach to collaborating, learning and adapting. As described by the Global Learning for Adaptive Management (GLAM) initiative, adaptive rigour is about ensuring that the data, information, methods, processes and systems that underpin adaptive management are robust, systematic and high‑quality. Key messages When faced with programmatic complexity, it is important to take an adaptive approach driven by continuous and iterative monitoring, evaluation and learning (MEL). USAID Wildlife Asia, which works to advance regional action towards ending illegal wildlife trafficking in Southeast Asia and China, has embraced this approach as a way of operationalising adaptive rigour. Throughout programming, MEL approaches should reflect the characteristics of adaptive rigour: comprehensiveness, usefulness, practicality, timeliness and support. Utilising performance monitoring and research in order to test and revise technical approaches and employing mixed methods to collect both qualitative and quantitative data, as well as looking for relevant lessons generated by others, can ensure access to the most useful information for decision-making throughout implementation. For adaptive management, it is not enough to monitor, evaluate and learn; it is also essential to pause and reflect in order to analyse and process evidence gained through MEL with colleagues and stakeholders to reach the right conclusions and make good decisions.